Peningkatan Keterampilan dan Karakter Guru terhadap Pembelajaran Sistem Among di SMPN 2 Kecamatan Suliki Kabupaten Lima Puluh Kota - Eldawati, Eldawati (Jurusan PIPS FKIP UMMY Solok, 2018)
This type of research is school action research. The purpose of the study was to determine the effectiveness of group training and guidance on improving the skills and character of teachers in learning through among systems at SMPN 2 Suliki District, Lima Puluh Kota District. The hypothesis used is the action hypothesis which is a temporary answer in the form of action (action) on the formulation of the problems set out in the planning of school action research. The research was carried out in 2 (two) cycles, each cycle held two meetings. The steps taken in each cycle are planning, implementing, observing and reflecting. Data obtained using tests, observations and questionnaires. The data obtained is analyzed and described to make a conclusion. After being given action in the form of group training and guidance in two cycles, it turns out that the actions taken have an impact on improving the skills and character of teachers in implementing learning through the system among the better. So that it does not rule out the possibility of a project that has the same characteristics as this research, this research can be used.